Pengajaran dan pembelajaran Bahasa Melayu di institusi pendidikan tinggi swasta di negeri Sarawak - Zamri Mahamod,; Celinea Lasan,; Nik Mohd. Rahimi Nik Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2009)
The purpose of this study is to investigate the perceptions of students at Private Higher Learning Institution (PHLI) in Sarawak on the teaching of Malay Language by their academic staff. More speciÞcally, this study is meant to Þnd out the perceptions of Bumiputera and non-Bumiputera students on the teaching of Malay Language in light of its teaching approaches, methods and materials, syllabus and evaluation. Questionnaire is used as the instrument of this study in order to collect data. The sample of this study consist of 218 Bumiputera and non-Bumiputera students who are currently following the Malay Language courses in Sarawak’s PHLI. Statistical inference is used to show the min variation between Bumiputera and non-Bumiputera students perception on the teaching of the Malay Language that they receive. Result from t-test indicate that there are no signiÞcant differences between the perceptions of Bumiputera and non-Bumiputera students with reference to the teaching approaches, materials and syllabus in the teaching of the Malay Language courses. In contrast, however with regards to the methods and evaluation being used, result from the t-test show that there are signiÞcant differences between perception of Bumiputera and non-Bumiputera students in the teaching of the Malay Langugae courses at these PHLI in Sarawak